FORMATION OF PROFESSIONAL COMPETENCE IN THE DEVELOPMENT OF COGNITIVE ABILITIES OF FUTURE TEACHERS - Bazarbaeva, Ayzhamal Kdirbaevna (SCIENCE and SOCIETY, 2026)
The article discusses the fact that in international research conducted by leading higher educational institutions and research centers around the world on the implementation of modern education of future specialists, special attention is paid to the criteria for the formation of professional competence in the development of cognitive abilities of future educators, the introduction of the requirements of international educational standards.
Keywords: Information and communication technology; cognitive ability; pedagogical competence; motivational; cognitive; operational; reflexive